Semantic and episodic memory in adults with temporal lobe epilepsy. Issue 6 (2nd November 2022) - Barrett Jones, Sarah; A. Miller, Laurie; Kleitman, Sabina; Nikpour, Armin; Lah, Suncica
Abstract: The primary aims were to (1) identify the factor structure of tests thought to measure semantic and episodic memory and (2) examine whether patterns of impairment would show a double dissociation between these two memory systems at an individual level in patients with temporal lobe epilepsy (TLE). The secondary aim was to explore the impact of epilepsy-related variables on performance. This retrospective study involved a cohort of 54 adults who had been diagnosed with TLE and had undergone a neuropsychological assessment that included four memory tests traditionally used to measure either semantic memory (picture naming, animal fluency) or episodic memory (story recall, word list recall) at a single epilepsy surgery center in Australia. Principal component analysis revealed two factors albeit with unexpected loadings. Picture naming and story recall loaded on one factor. Animal fluency and word list recall loaded on another factor. There was no evidence of a double dissociation between semantic and episodic memory at an individual level. Left hemisphere seizure focus and early age of seizure onset related to worse performance on word list recall, picture naming and animal fluency, respectively. Our study highlights the importance of caution when interpreting the results of neuropsychological assessments, as not all putative tests of semantic and episodic memory may necessarily be measuring the same construct. Future directions for research are also considered.